Integrate the following w.r.t. x : 1sinx⋅(3+2cosx) - Mathematics and Statistics

Advertisements
Advertisements
Sum

Integrate the following w.r.t. x : `(1)/(sinx*(3 + 2cosx)`

Advertisements

Solution

Let I = `(1)/(sinx*(3 + 2cosx))*dx`

= `int sinx/(sin^2x*(3 + 2cosx))*dx`

= `int sinx/((1 - cos^2x)(3 + 2cosx))*dx`

= `int sinx/((1 - cosx)(1 + cosx)(3 + 2cosx))*dx`

Put cos x = t
∴ – sinx.dx = dt
∴ sinx.dx = – dt

∴ I = `int (1)/((1 - t)(1 + t)(3 + 2t))*(-dt)`

= `int (-1)/((1 - t)(1 + t)(3 + 2t))*dt`

Let `(-1)/((1 - t)(1 + t)(3 + 2t)) = "A"/(1 - t) + "B"/(1 + t) + "C"/(3 + 2t)`

∴ – 1 = A(1 + t)(3 + 2t) + B(1 - t)(3 + 2t) + C(1 - t)(1 + t)
Put 1 – t = 0, i.e. t = 1, we get
– 1 = A(2)(5) + B(0)(5) + C(0)(2)

∴ – 1 = 10A

∴ A = `(-1)/(10)`
Put 1 + t = 0, i.e. t = – 1, we get
– 1 = A(0)(1) + B(2)(1) + C(2)(0)

∴ – 1 = 2B

∴ B = `-(1)/(2)`

Put 3 + 2t = 0, i.e. t = `-(3)/(2)`, we get

– 1 = `"A"(-1/2)(0) + "B"(5/2)(0) + "C"(5/2)(-1/2)`

∴ –  1 = `-(5)/(4)"C"`

∴ C = `(4)/(5)`

∴ `(-1)/((1 - t)(1 + t)(3 + 2t)) = (((-1)/(10)))/(1 - t) + ((-1/2))/(1 + t) + ((4/5))/(3 + 2t)`

∴ I = `int [(((-1)/10))/(1 - t) + ((-1/2))/(1 + t) + ((4/5))/(3 + 2t)]*dt`

= `-(1)/(10) int 1/(1 - t)*dt - (1)/(2) int 1/(1 + t)*dt + (4)/(5) int 1/(3 + 2t)*dt`

= `-(1)/(10) (log|1 - t|)/(-1) - (1)/(2) log | 1 + t| + 4/5 (log|3 + 2t|)/(2) + c`

= `(1)/(10)log|1 - cosx| - (1)/(2)log|1 + cosx| + (2)/(5)log|3 + 2cos| + c`.

  Is there an error in this question or solution?
Chapter 3: Indefinite Integration - Exercise 3.4 [Page 145]

APPEARS IN

RELATED QUESTIONS

Evaluate : `int x^2/((x^2+2)(2x^2+1))dx` 


Find : `int x^2/(x^4+x^2-2) dx`


Evaluate:

`int x^2/(x^4+x^2-2)dx`


Find: `I=intdx/(sinx+sin2x)`


Integrate the rational function:

`x/((x + 1)(x+ 2))`


Integrate the rational function:

`x/((x-1)(x- 2)(x - 3))`


Integrate the rational function:

`(2x)/(x^2 + 3x + 2)`


Integrate the rational function:

`(1 - x^2)/(x(1-2x))`


Integrate the rational function:

`x/((x^2+1)(x - 1))`


Integrate the rational function:

`(3x + 5)/(x^3 - x^2 - x + 1)`


Integrate the rational function:

`(2x - 3)/((x^2 -1)(2x + 3))`


Integrate the rational function:

`(5x)/((x + 1)(x^2 - 4))`


Integrate the rational function:

`(x^3 + x + 1)/(x^2 -1)`


Integrate the rational functions `1/(x^4 - 1)`


Integrate the rational functions `1/(x(x^n + 1))` [Hint: multiply numerator and denominator by xn − 1 and put xn = t]


Integrate the rational functions `((x^2 +1)(x^2 + 2))/((x^2 + 3)(x^2+ 4))`


Integrate the rational functions  `(2x)/((x^2 + 1)(x^2 + 3))`


Integrate the rational functions `1/(x(x^4 - 1))`


Choose the correct answer `int (dx)/(x(x^2 + 1))` equal

A. `log |x| - 1/2 log (x^2 + 1) + C`

B. `log |x| + 1/2 log(x^2 + 1) + C`

C. `- log|x| + 1/2 log (x^2 + 1) + C`

D. `1/2 log|x| + log(x^2 + 1)+ C`


Evaluate : `∫(x+1)/((x+2)(x+3))dx`


Find `int(e^x dx)/((e^x - 1)^2 (e^x + 2))`


Find : 

`∫ sin(x-a)/sin(x+a)dx`


Integrate the following w.r.t. x : `(x^2 + 2)/((x - 1)(x + 2)(x + 3)`


Integrate the following w.r.t. x : `x^2/((x^2 + 1)(x^2 - 2)(x^2 + 3))`


Integrate the following w.r.t. x : `(12x + 3)/(6x^2 + 13x - 63)`


Integrate the following w.r.t. x : `(2x)/(4 - 3x - x^2)`


Integrate the following w.r.t. x : `(x^2 + x - 1)/(x^2 + x - 6)`


Integrate the following w.r.t. x : `(6x^3 + 5x^2 - 7)/(3x^2 - 2x - 1)`


Integrate the following w.r.t. x : `(12x^2 - 2x - 9)/((4x^2 - 1)(x + 3)`


Integrate the following w.r.t. x : `(1)/(x(x^5 + 1)`


Integrate the following w.r.t. x : `(2x)/((2 + x^2)(3 + x^2)`


Integrate the following w.r.t. x : `2^x/(4^x - 3 * 2^x - 4`


Integrate the following w.r.t. x : `(3x - 2)/((x + 1)^2(x + 3)`


Integrate the following w.r.t. x : `(1)/(x(1 + 4x^3 + 3x^6)`


Integrate the following w.r.t. x : `(1)/(x^3 - 1)`


Integrate the following w.r.t. x : `((3sin - 2)*cosx)/(5 - 4sin x - cos^2x)`


Integrate the following w.r.t. x : `(1)/(sinx + sin2x)`


Integrate the following w.r.t. x : `(1)/(2sinx + sin2x)`


Integrate the following w.r.t. x : `(1)/(sin2x + cosx)`


Integrate the following w.r.t. x : `(2log x + 3)/(x(3 log x + 2)[(logx)^2 + 1]`


Choose the correct options from the given alternatives :

If `int tan^3x*sec^3x*dx = (1/m)sec^mx - (1/n)sec^n x + c, "then" (m, n)` =


Integrate the following w.r.t. x: `(2x^2 - 1)/(x^4 + 9x^2 + 20)`


Integrate the following w.r.t. x: `(x^2 + 3)/((x^2 - 1)(x^2 - 2)`


Integrate the following with respect to the respective variable : `(cos 7x - cos8x)/(1 + 2 cos 5x)`


Integrate the following with respect to the respective variable : `cot^-1 ((1 + sinx)/cosx)`


Integrate the following w.r.t.x : `x^2/sqrt(1 - x^6)`


Integrate the following w.r.t.x : `(1)/((1 - cos4x)(3 - cot2x)`


Integrate the following w.r.t.x : `x^2/((x - 1)(3x - 1)(3x - 2)`


Integrate the following w.r.t.x : `(1)/(sinx + sin2x)`


Integrate the following w.r.t.x :  `sec^2x sqrt(7 + 2 tan x - tan^2 x)`


Integrate the following w.r.t.x : `(x + 5)/(x^3 + 3x^2 - x - 3)`


Evaluate: `int (2"x" + 1)/(("x + 1")("x - 2"))` dx


Evaluate: `int 1/("x"("x"^"n" + 1))` dx


Evaluate: `int (5"x"^2 + 20"x" + 6)/("x"^3 + 2"x"^2 + "x")` dx


Choose the correct alternative from the following.

`int "dx"/(("x - 8")("x + 7"))`= 


State whether the following statement is True or False.

For `int ("x - 1")/("x + 1")^3  "e"^"x" "dx" = "e"^"x"` f(x) + c, f(x) = (x + 1)2.


Evaluate: `int (1 + log "x")/("x"(3 + log "x")(2 + 3 log "x"))` dx


`int ((2x - 7))/sqrt(4x- 1)  "d"x`


`int x^7/(1 + x^4)^2  "d"x`


`int sqrt(4^x(4^x + 4))  "d"x`


`int (7 + 4x + 5x^2)/(2x + 3)^(3/2)  "d"x`


`int sqrt((9 + x)/(9 - x))  "d"x`


`int 1/(4x^2 - 20x + 17)  "d"x`


`int 1/(2 +  cosx - sinx)  "d"x`


`int sec^2x  "d"x`


`int sin(logx)  "d"x`


`int sec^2x sqrt(tan^2x + tanx - 7)  "d"x`


`int "e"^(sin^(-1_x))[(x + sqrt(1 - x^2))/sqrt(1 - x^2)] "d"x`


`int "e"^x ((1 + x^2))/(1 + x)^2  "d"x`


`int (x^2 + x -1)/(x^2 + x - 6)  "d"x`


`int (6x^3 + 5x^2 - 7)/(3x^2 - 2x - 1)  "d"x`


`int ("d"x)/(2 + 3tanx)`


`int (3x + 4)/sqrt(2x^2 + 2x + 1)  "d"x`


`int x^3tan^(-1)x  "d"x`


`int x sin2x cos5x  "d"x`


`int (x + sinx)/(1 - cosx)  "d"x`


`int (5"e"^x)/(("e"^x + 1)("e"^(2x) + 9))  "d"x`


`int (sin2x)/(3sin^4x - 4sin^2x + 1)  "d"x`


`int (3"e"^(2x) + 5)/(4"e"^(2x) - 5)  "d"x`


`int  ((2logx + 3))/(x(3logx + 2)[(logx)^2 + 1])  "d"x`


Choose the correct alternative:

`int sqrt(1 + x)  "d"x` =


Choose the correct alternative:

`int (x + 2)/(2x^2 + 6x + 5) "d"x = "p"int (4x + 6)/(2x^2 + 6x + 5) "d"x + 1/2 int 1/(2x^2 + 6x + 5)"d"x`, then p = ?


Choose the correct alternative:

`int ((x^3 + 3x^2 + 3x + 1))/(x + 1)^5 "d"x` =


`int (5(x^6 + 1))/(x^2 + 1) "d"x` = x5 – ______ x3 + 5x + c


If f'(x) = `1/x + x` and f(1) = `5/2`, then f(x) = log x + `x^2/2` + ______ + c


State whether the following statement is True or False:

For `int (x - 1)/(x + 1)^3  "e"^x"d"x` = ex f(x) + c, f(x) = (x + 1)2


Evaluate `int (2"e"^x + 5)/(2"e"^x + 1)  "d"x`


Evaluate `int x log x  "d"x`


`int x/((x - 1)^2 (x + 2)) "d"x`


`int (3"e"^(2"t") + 5)/(4"e"^(2"t") - 5)  "dt"`


If `int(sin2x)/(sin5x  sin3x)dx = 1/3log|sin 3x| - 1/5log|f(x)| + c`, then f(x) = ______


If `intsqrt((x - 7)/(x - 9)) dx = Asqrt(x^2 - 16x + 63) + log|x - 8 + sqrt(x^2 - 16x + 63)| + c`, then A = ______


Verify the following using the concept of integration as an antiderivative

`int (x^3"d"x)/(x + 1) = x - x^2/2 + x^3/3 - log|x + 1| + "C"`


Evaluate the following:

`int (x^2"d"x)/(x^4 - x^2 - 12)`


Evaluate the following:

`int_"0"^pi  (x"d"x)/(1 + sin x)`


Evaluate the following:

`int (2x - 1)/((x - 1)(x + 2)(x - 3)) "d"x`


Evaluate the following:

`int sqrt(tanx)  "d"x`  (Hint: Put tanx = t2)


The numerator of a fraction is 4 less than its denominator. If the numerator is decreased by 2 and the denominator is increased by 1, the denominator becomes eight times the numerator. Find the fraction.


Evaluate: `int (dx)/(2 + cos x - sin x)`


Evaluate: `int_-2^1 sqrt(5 - 4x - x^2)dx`


If f(x) = `int(3x - 1)x(x + 1)(18x^11 + 15x^10 - 10x^9)^(1/6)dx`, where f(0) = 0, is in the form of `((18x^α + 15x^β - 10x^γ)^δ)/θ`, then (3α + 4β + 5γ + 6δ + 7θ) is ______. (Where δ is a rational number in its simplest form)


Let g : (0, ∞) `rightarrow` R be a differentiable function such that `int((x(cosx - sinx))/(e^x + 1) + (g(x)(e^x + 1 - xe^x))/(e^x + 1)^2)dx = (xg(x))/(e^x + 1) + c`, for all x > 0, where c is an arbitrary constant. Then ______.


`int 1/(x^2 + 1)^2 dx` = ______.


If `int dx/sqrt(16 - 9x^2)` = A sin–1 (Bx) + C then A + B = ______.


If `int 1/((x^2 + 4)(x^2 + 9))dx = A tan^-1  x/2 + B tan^-1(x/3) + C`, then A – B = ______.


If `intsqrt((x - 5)/(x - 7))dx = Asqrt(x^2 - 12x + 35) + log|x| - 6 + sqrt(x^2 - 12x + 35) + C|`, then A = ______.


Evaluate: `int (2x^2 - 3)/((x^2 - 5)(x^2 + 4))dx`


Find : `int (2x^2 + 3)/(x^2(x^2 + 9))dx; x ≠ 0`.


Evaluate: 

`int 2/((1 - x)(1 + x^2))dx`


Share
Notifications



      Forgot password?
Use app×